Long-term retention of ECM hydrogel after implantation into a sub-acute stroke cavity reduces lesion volume - Ghuman, Harmanvir (Acta Biomater, 2017)
Salvaging or functional replacement of damaged tissue caused by stroke in the brain remains a major therapeutic challenge. In situ gelation and retention of a hydrogel bioscaffold composed of 8 mg/mL extracellular matrix (ECM) can induce a robust invasion of cells within 24 hours and potentially promote a structural remodeling to replace lost tissue. Herein, we demonstrate a long-term retention of ECM hydrogel within the lesion cavity. A decrease of approximately 32% of ECM volume is observed over 12 weeks. Lesion volume, as measured by magnetic resonance imaging and histology, was reduced by 28%, but a battery of behavioral tests (bilateral asymmetry test; footfault; rotameter) did not reveal a therapeutic or detrimental effect of the hydrogel. Glial scarring and peri-infarct astrocytosis were equivalent between untreated and treated animals, potentially indicating that permeation into host tissue is required to exert therapeutic effects. These results reveal a marked difference of biodegradation of ECM hydrogel in the stroke-damaged brain compared to peripheral soft tissue repair. Further exploration of these structure-function relationships is required to achieve a structural remodeling of the implanted hydrogel, as seen in peripheral tissues, to replace lost tissue and promote behavioral recovery.